2022
DOI: 10.1126/sciimmunol.adf1421
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 spike conformation determines plasma neutralizing activity elicited by a wide panel of human vaccines

Abstract: Numerous safe and effective COVID-19 vaccines have been developed worldwide that utilize various delivery technologies and engineering strategies. We show here that vaccines containing prefusion-stabilizing S mutations elicit antibody responses in humans with enhanced recognition of S and the S 1 subunit relative to postfusion S, as compared to vaccines lacking these mutations or natural infection. Prefusion S and S 1 antibody binding titers positively and equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 147 publications
7
44
0
Order By: Relevance
“…Furthermore, since the RBD contains conserved epitopes that are recognized across most circulating clades, specifically targeting conserved epitopes within the RBD may generate SARS-CoV-2 vaccines with broader cross-variant neutralization and thus protective activity [ 141 , 142 ]. This is in line with the findings that the cross-neutralization of SARS-CoV-2 variants is determined by RBD-specific antibodies [ 125 ] and that RBD-targeting neutralizing antibody cocktails have the potential to protect their recipients from infection with variants of Omicron [ 143 ].…”
Section: Importance Of Glycoprotein Stabilization For Vaccine Develop...supporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, since the RBD contains conserved epitopes that are recognized across most circulating clades, specifically targeting conserved epitopes within the RBD may generate SARS-CoV-2 vaccines with broader cross-variant neutralization and thus protective activity [ 141 , 142 ]. This is in line with the findings that the cross-neutralization of SARS-CoV-2 variants is determined by RBD-specific antibodies [ 125 ] and that RBD-targeting neutralizing antibody cocktails have the potential to protect their recipients from infection with variants of Omicron [ 143 ].…”
Section: Importance Of Glycoprotein Stabilization For Vaccine Develop...supporting
confidence: 84%
“…These analyses were performed with human sera from individuals that were not exposed to SARS-CoV-2 before being immunized with two doses of the Moderna/NIAID mRNA-1273, Pfizer/BioNTech Comirnaty, Novavax NYX-CoV2373, Janssen /Johnson & Johnson Ad26.CoV2.S or Astra-Zeneca/Oxford AZD1222, Gamaleya Sputnik V and Sinopharm CoVilo/BBIBP-CorV vaccines ( Table 1 ). Superior immune responses with the S ‘2P’-stabilized vaccines over the non-stabilized native S vaccines were reported, based on the correlation between antibody binding titers and neutralization potency, as well as the contribution of RBD- and NTD-specific antibodies to the cross-neutralization of SARS-CoV-2 variants [ 125 ]. Neutralizing antibody titers were also positively correlated with NTD- and RBD-specific binding titers, which is in line with both domains acting as the main target for the generation of neutralizing antibodies upon infection and vaccination [ 107 , 126 , 127 , 128 ].…”
Section: Importance Of Glycoprotein Stabilization For Vaccine Develop...mentioning
confidence: 99%
“…10b-e). As the SARS-CoV-2 S 1 subunit, especially the RBD, accounts for most of the infection-or vaccine-elicited serum neutralizing activity [40][41][42] and several potent MERS-CoV neutralizing antibodies target the RBD, our findings suggest that immunity to either SARS-CoV-2 or MERS-CoV would not elicit appreciable titres of cross-neutralizing antibodies owing to marked divergence of their RBDs 28,36,43 .…”
Section: Spike Architecture and Antigenicitymentioning
confidence: 82%
“…Additionally, the rabbit anti-spike serum was able to generate a strong neutralizing effect, similar to the effect generated by immunization with the RBD gene which also suggested that immune response was focused to a region other than RBD, such as the N-terminal domain (NTD). The NTD has been described as an important region for neutralization of SARS-CoV-2 or other CoVs, where antibodies may cause conformational changes in the spike protein, that are required for fusion or interactions with cell receptors, in both live virus and pseudovirus assays [ 54 , 55 , 56 , 57 ]. If this proves to be true, a focus away from the RBD may be highly desirable for protection against multiple VOCs.…”
Section: Discussionmentioning
confidence: 99%